Uji Aktivitas Ekstrak Etanol Daun Singkong (Manihot esculenta Crantz) Terhadap Penyembuhan Luka Pada Kelinci - Sekar Sri Sukmawati; Siwi Hastuti; Sri Rejeki - Politeknik Kesehatan Bhakti Mulia (Indonesian Journal on Medical Science, 2021)
Abstract : An incision is an injury caused by direct contact of the body with sharp objects. Cassava leaves (Manihot esculenta Crantz) are a medicinal plant known to contain compounds that play a role in wound healing, such as vitamin C, flavonoids, triterpenoids, tannins and saponins. This study aims to determine the effect of ethanol extract of cassava leaves on the healing of cuts in rabbits. The ethanol extract of cassava leaves was prepared by maceration using 70% ethanol as a solvent. The wound healing test in rabbits was divided into 5 treatment groups, namely the positive control, the negative control, and test groups were given ethanol extract of cassava leaves concentration of 5%, 10% and 20%. Making an incision using a scalpel which is sliced into the back of the rabbit for 5 incisions. Rabbits were observed every day for one week with statistical analysis One Way ANOVA test followed by LSD test with Post Hoc Test. The ethanol extract of cassava leaves with a concentration of 5% 10% and 20% has the effect of wound healing.The concentration of 5% is (9.71 ± 0.17)%, the concentration of 10% is (17.19 ± 0.05)%, and a concentration of 20% is (23.24 ± 0.04)%. The results of the LSD test with the Post Hoc Test showed that there was no significant difference between the ethanol extract of 20% cassava leaves and the positive control, which means that the ethanol extract of cassava leaves can be used as wound healing in rabbits.Key words : Cutlet wounds, cassava leaves, Manihot esculenta Crantz, ethanol extract of cassava leaves.Abstrak : Luka sayat adalah cedera yang disebabkan oleh kontak langsung tubuh dengan benda – benda tajam. Daun singkong (Manihot esculenta Crantz) merupakan salah satu tanaman obat yang diketahui mengandung senyawa yang berperan dalam penyembuhan luka seperti vitamin C, flavonoid, triterpenoid, tanin dan saponin. Penelitian ini bertujuan untuk mengetahui ekstrak etanol daun singkong berpengaruh terhadap terhadap penyembuhan luka sayat pada kelinci. Ekstrak etanol daun singkong dibuat dengan maserasi menggunakan pelarut etanol 70%. Uji penyembuhan luka pada kelinci yang dibagi dalam 5 kelompok perlakuan yaitu kelompok kontrol positif, kontrol negatif dan kelompok uji ekstrak etanol daun singkong konsentrasi 5%, 10% dan 20%. Pembuatan luka sayat menggunakan pisau bedah yang disayat pada punggung kelinci masing – masing kelinci 5 sayatan. Kelinci diamati tiap hari selama satu minggu dengan analisis statistik uji One Way ANOVA dilanjut uji LSD dengan Post Hoc Test. Ekstrak etanol daun singkong konsentrasi 5% 10% dan 20% memiliki pengaruh penyembuhan luka konsentrasi 5% adalah (9,71±0,17)%, konsentrasi 10% adalah (17,19±0,05) %, dan konsentasi 20% adalah (23,24±0,04)%. Hasil uji LSD dengan Post Hoc Test menunjukkan bahwa tidak ada perbedaan yang signifikan antara ekstrak etanol daun singkong 20% dengan kontrol positif, yang berarti ekstrak etanol daun singkong dapat digunakan sebagai penyembuhan luka pada kelinci.Kata kunci : Luka Sayat, Daun singkong, Manihot esculenta Crantz, ekstrak etanol daun singkong.